Creating safer organisations: practical steps to prevent the abuse of children by those working with them - Erooga, Marcus (NSPCC/Wiley series in protecting children, 2012)
"This is an accessible resource for those seeking to ensure that they have taken all possible steps to safeguard the children and young people they are responsible for"--Provided by publisher